Transformasi Digital Aplikasi Rencana Kegiatan dan Anggaran Sekolah (ARKAS) untuk Meningkatkan Transparansi dan Akuntabilitas Keuangan Sekolah - Mubarok, Yasid; Sulistiyarini, Sulistiyarini; Basri, M. (Jurnal Ilmiah Global Education, 2025)
This research is motivated by the demand for transparency and accountability in the management of education funds, particularly the School Operational Assistance (BOS) funds, in the digital era. The School Activity and Budget Plan Application (ARKAS) emerges as a strategic innovation to enhance information disclosure and the effectiveness of school financial governance. The purpose of this study is to describe the implementation of ARKAS, analyze its contribution to transparency and accountability, identify the challenges faced by schools, and explore strategies for optimizing its utilization. The research method employed is a qualitative case study with a descriptive approach. Data were collected through in-depth interviews with principals, treasurers, operators, supervisors, and school committees, complemented by participatory observation and financial document analysis. Data validation was carried out using triangulation, member checking, and peer debriefing. The findings indicate that ARKAS strengthens transparency by providing stakeholders with access to financial data and improves accountability through systematic digital reporting. However, obstacles such as limited internet networks, inadequate devices, and low digital literacy remain major challenges. Optimization strategies include technical training, intensive mentoring, as well as strengthening both internal and external monitoring. In conclusion, ARKAS is not merely a technical tool but a digital transformation instrument that promotes school financial governance to become more transparent, accountable, efficient, and participatory.